Isolation, Cloning and Sequence Analysis of Enolase Enzyme Encoding Gene from Theileria annulata for Assessment of Important Residues of This Enzyme - Akat, Ayberk; Aktas, Munir; Dumanli, Nazir; Turgut-Balik, Dilek (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
Drug resistance against one of the important antitheilerial drugs has been reported for the first time in 2010. For the aim of developing new antitheilerial drugs or vaccines, enolase gene was isolated from the genomic DNA of Theileria annulata, cloned for the first time in the literature and analyzed at nucleotide and amino acid levels by using different web based tools. These analyses showed that the gene was consisted of 1365 nucleotides including an intron sequence placed between residues 40-41. Restriction enzyme mapping analysis of the cloned gene showed that, base pair changes in TaENO Elazig strain caused differences on cutting and non-cutting restriction enzymes compared to the Ankara strain. These differences may help the identification of different strains by restriction mapping and it may be possible to determine the geological distribution of T. annulata strains in any region. As the comparison of enolase gene sequences from T. annulata and the muscle enolase isoform of the host Bos taurus was made, four different insertions in T. annulata enolase that do not exist in B. taurus enolase was reported as an important discovery of this study. The modeling studies on T. annulata enolase gene showed that these insertions constituted loops that do not exist in B. taurus enolase, suggesting that these loops could be specific binding sites for enzyme inhibitors.
Theileria annulata'nin enolaz enzimini kodlayan geninin, önemli rezidülerinin de?erlendirilmesi amaci{dotless}yla İzolasyonu, klonlanmasi{dotless} ve dizi analizinin yapi{dotless}lmasi{dotless}
Keywords: Theileria annulata; Enolase; Strain identification; Antitheilerial drugs; Structure based drug design; Protein homology modeling